1959
DOI: 10.1161/01.cir.19.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hematoma during Anticoagulant Therapy

Abstract: Spinal epidural hematoma complicated the course of anticoagulant therapy of cerebrovascular disease in a patient in whom observations of multiple aspects of coagulation had been obtained. Examination of this case and a review of the literature allow delineation of a syndrome that should aid in early diagnosis of spinal epidural hematoma. It is clear that coumarin derivatives induce multiple coagulation defects, which vary quantitatively and qualitatively with time. Contemporary evaluation of the benefits and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In our second case the epidural haemorrhage was apparently related to anticoagulant therapy, though this particular complication is extremely rare (Cloward and Yuhl, 1955;Alderman, 1956;Winer, Horenstein, and Starr, 1959). Devanney and Osher (1952), at the clinicopathological meeting of Cincinnati General Hospital, presented a patient 62 years of age who was on anticoagulant therapy for thrombophlebitis of the leg, who developed severe backache, bilateral posterior radicular pain, which progressing gradually resulted in paraparesis and urinary retention.…”
Section: Discussionmentioning
confidence: 77%
“…In our second case the epidural haemorrhage was apparently related to anticoagulant therapy, though this particular complication is extremely rare (Cloward and Yuhl, 1955;Alderman, 1956;Winer, Horenstein, and Starr, 1959). Devanney and Osher (1952), at the clinicopathological meeting of Cincinnati General Hospital, presented a patient 62 years of age who was on anticoagulant therapy for thrombophlebitis of the leg, who developed severe backache, bilateral posterior radicular pain, which progressing gradually resulted in paraparesis and urinary retention.…”
Section: Discussionmentioning
confidence: 77%
“…Winer et al 11, reviewed aft cases of spontaneous epidural haematomata reported to that time and found that approximately one-fourth of the cases in the literature had coagulation defects, including those with blood dyscrasias. In his review of the literature on spontaneous epidural haematoma, Gold 12 found that in onequarter of the reported cases coagulation defects had been present, mostly in elderly patients on long-term anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The association of spinal epidural hematoma with warfarin therapy has been described in literature, although many of the reported cases were anticoagulated within the therapeutic range. [1] SSEH should be suspected in any patient receiving anticoagulants who presents with local or referred back pain associated with limb weakness, sensory deficits or urinary retention. A 21-year-old male with SSEH who was receiving warfarin for hyperhomocysteinemia with sagittal sinus thrombosis is presented in this letter.…”
Section: Sirmentioning
confidence: 99%
“…[3] The term SSEH is given if no cause can be identified, which occurs in 40-50% of the cases. [1,2] Spinal epidural hematoma is believed to result from rupture of fragile epidural venous plexus after the sudden increase in intra-thoracic or intra-abdominal pressure. [1] An average of 3.8 spinal segments is involved.…”
Section: Anticoagulant Induced Spontaneous Spinal Epidural Hematomamentioning
confidence: 99%